Taxonomic checklist of the pteridophytes of Rajkandi Reserve Forest, Moulvibazar, Bangladesh - Haque, AKM Kamrul; Khan, Saleh Ahammad; Uddin, Sarder Nasir; Rahim, Mohammod Abdur (Jahangirnagar University Journal of Biological Sciences, 2017)
Pteridophytes growing in the Rajkandi Reserve Forest of Moulvibazar district were indentified and a total of 52 species belonging to 30 genera of 20 families have been documented. The family Pteridaceae with nine species was found to be the largest, which was followed by Polypodiaceae with seven, Tectariaceae with six and Thelypteridaceae with five species. The genus Pteris with six species was found as the largest, which was followed by Tectaria with five and Bolbitis, Lygodium and Selaginella, each with 3 species, and the rest of the genera consisted of two or one species. Most of the species were recorded from the woodlands and three species, viz., Tectaria chattagramica and Cyathea gigantea enlisted in Red Data Book of Bangladesh (Khan et al., 2001), were found as common in this reserve forest. Jahangirnagar University J. Biol. Sci. 5(2): 27-40, 2016 (December)